On the inactivation of bacteria by singlet oxygen — another view - Parker, J.G. (Biochimica et biophysica acta, 1993)
Midden and Dahl, in a recent paper [1], have presented important data on the inactivation of bacteria by singlet oxygen. In analyzing the data, use was made of a theory published earlier by the present author [4]. The purpose of this paper is to point out that theory and experiment can be brought into better agreement by assuming that the interaction of singlet oxygen with the bacteria takes place in an essentially lipid environment rather than aqeous.